Incidencia de Variantes Anatómicas del Frenillo Labial Superior en los y las Estudiantes de 18 a 30 años de edad de la Universidad Nacional de Loja Modalidad de Estudios Presencial en el periodo mayo - julio de 2014. - Torres Estrada, Stefanía Nathaly (2014)
The labial frenulum is a normal structure consisting of a fold of mucosa located in the midline, linking one hand the inner surface of the lip lip and on the other, the gum may have some variations in their anatomy, as its shape, size and location. The Anatomical variants Lip frenulum Superior are very frequent, and little considered, so that the present research has as its main objective; Recognize Anatomical Variants Superior Lip Frenulum in the students of 18-30 years of age from the National University of Loja face modality studies in the period May - July 2014, and its analysis of descriptive and cross-sectional whose data thrown enunciated that of the 894 people studied, 225 people have some type of anatomical variant of the Superior Labial frenulum. By streamlining the data collected it was observed that the types of Anatomic Variants that was found in the population were: Bridle Lip Superior Appendix represented by 79%, Bridle Lip Superior nodule represented by 17%, Bridle Tectolabial with 2% and finally Bridle Lip Lip Frenulum Superior Double Superior Bifida and represented by 1%, the incidence of major anatomic variations in men than in women. Keywords: Lip Frenulum, Anatomic Variant, fold, tectolabial